2021
DOI: 10.14710/nmjn.v11i2.28881
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Interventions of Pressure Injury Prevention Bundles of Care in Critically Ill Patients: A Systematic Review

Abstract: Background: Many studies on pressure injury prevention bundles have been conducted outside the Intensive Care Unit (ICU). The bundles, which include multi interventions, have proven effective in reducing pressure ulcer incidents compared to a single intervention. However, the existing review studies on pressure injury prevention in ICUs still only investigate a single intervention rather than multi interventions. Only few reviews, to our knowledge, involves prevention bundle strategies in the ICU.Purpose: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Several other studies that also used VCO as a topical agent for the prevention of pressure sores explained that there was an effect of changing position and VCO massage on the prevention of decubitus ulcers in bedridden patients at Tangerang District General Hospital. The risk of decubitus ulcers after changing position and VCO massage decreased compared to before changing position and VCO massage (Demir & Kasapoğlu, 2008;Trisnaningtyas et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several other studies that also used VCO as a topical agent for the prevention of pressure sores explained that there was an effect of changing position and VCO massage on the prevention of decubitus ulcers in bedridden patients at Tangerang District General Hospital. The risk of decubitus ulcers after changing position and VCO massage decreased compared to before changing position and VCO massage (Demir & Kasapoğlu, 2008;Trisnaningtyas et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Massage is a therapy that has various benefits for the body's organ systems, including improving the function of the skin, muscle tissue, bone growth, joint motion, and nerve tissue. If massage is done for a certain time, it will have a relaxing effect thereby reducing pressure on the body, one of which is using the effleurage technique (Darmareja et al, 2020;Trisnaningtyas et al, 2021). The effleurage technique is performed by wiping the body once or twice a day which is believed to minimize the occurrence of decubitus ulcers (Phasar, Imran.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 17 studies exploring pressure injury prevention bundles for critically ill patients mostly found decreased incidence of pressure injuries, however a metaanalysis could not be taken due to the variation in methods. 58 The pre/post studies evaluated implementation of local guidelines and education, multi-component 'bundles' or programs, or structured skin care protocols. Studies on guideline and/or education interventions found improved nurses' or care staff knowledge, 59,60 in addition to improvement of dry skin and decreased TEWL.…”
Section: Health Service Interventionsmentioning
confidence: 99%